2012
DOI: 10.1111/j.1750-3841.2012.02943.x
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic Study of Sasa veitchii Extract as a Radical Scavenger and an Antioxidant

Abstract: We determined the stoichiometric number and the rate constants of bamboo extracts using the method that was devised in determining the antioxidant activity of mixtures. This is the first study of bamboo extracts as an antioxidant that reports the stoichiometric and kinetic results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Recently, extracts of bamboo leaves were reported to have multiple biological activities including antioxidant activity and cancer prevention [ 3 , 4 ]. Furthermore, previous studies have demonstrated the antitumor [ 5 ], antioxidant [ 1 , 6 ], antiviral [ 7 ], anti-inflammatory [ 8 ], and anti-allergic [ 9 ] activities of the extract.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, extracts of bamboo leaves were reported to have multiple biological activities including antioxidant activity and cancer prevention [ 3 , 4 ]. Furthermore, previous studies have demonstrated the antitumor [ 5 ], antioxidant [ 1 , 6 ], antiviral [ 7 ], anti-inflammatory [ 8 ], and anti-allergic [ 9 ] activities of the extract.…”
Section: Introductionmentioning
confidence: 99%
“…The leaves contain lignin, polysaccharides, and chlorophyll, among other components [ 12 , 13 ], and are used as a folk medicine for stomachaches. Recently, Kumazasa extract has been observed to have various pharmacological effects, such as antioxidant [ 14 ], anti-inflammatory [ 15 , 16 ], antibacterial [ 17 , 18 ], and anticancer effects [ 19 ], and to be useful as a health food material. In addition, Kumazasa extract has been reported to have a wound healing effect [ 20 ], and its effect on the skin is also attracting attention.…”
Section: Introductionmentioning
confidence: 99%